Pengaruh Kemudahan, Manfaat dan Keamanan terhadap Minat Menggunakan E-Wallet pada Masyarakat Parit Boom Kecamatan Nipah Panjang - Hansen Rusliani; Rendi Apriyadi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to determine the effect of convenience, benefits and security on the interest in using e-wallets in the Parit Boom community, Nipah Panjang District. The method used in this study is a quantitative method, and the data analysis method used is multiple regression, t-test and f-test. The sample in this study was 67 samples of the Parit Boom community, Nipah Panjang District, by distributing a Likert scale questionnaire. The test results obtained from the t-test show that the convenience variable (X1) has a significant effect on the interest in using e-wallets (Y). This is evidenced by the calculated T value> Ttable, which is 3,287> 2.75 and a significant value of 002 <0.05 so that it can be concluded that Ho is rejected a.nd Ha. is a.ccepted, while the benefit va.ria.ble (X2) ha.s a. significa.nt effect on the interest in using e-wa.llets (Y). This is evidenced by the ca.lcula.ted T va.lue > Tta.ble, which is 3.54 > 2.75 a.nd a. significa.nt va.lue of 002 < 0.05, so Ho is rejected a.nd Ha. is a.ccepted, so the benefit va.ria.ble (X2) ha.s a.n effect on the interest in using e-wa.llet (Y). While the va.ria.ble (X3) does not ha.ve a. significa.nt effect on the interest in using e-wa.llet (Y). This is evidenced by the ca.lcula.ted T va.lue < Tta.ble, which is 0.220 < 2.75 a.nd a. significa.nt va.lue of 826 > 0.05, so it ca.n be concluded tha.t Ho is a.ccepted a.nd Ha. is rejected, so the security va.ria.ble (X2) ha.s a. significa.nt effect on the interest in using e-wa.llet (Y). The test results obta.ined from the f test show tha.t the va.ria.bles of convenience, benefits a.nd security simulta.neously ha.ve a.n effect on the interest in using e-wa.llet. This is evidenced by the ca.lcula.ted f va.lue > fta.ble, which is 8.292 > 1.998 a.nd a. significa.nt va.lue of 0.01 < 0.05